Theory of concentration distribution over the surface of axisymmetrical receiver in cylindrical parabolic mirror solar energy concentrator. (November 2020) - Arbuzov, Yuri D.; Evdokimov, Vladimir M.; Shepovalova, Olga V.
Abstract: This work is devoted to develop the theory of concentration distribution of radiation over the receiver surface in cylindrical parabolic concentrator of radiation with axisymmetrical (cylindrical) radiation receiver has been studied. The results will make it possible to estimate concentration distribution over the radiation receiver surface and to associate output characteristics of concentrator unit for various combinations of design parameters at the stage of engineering, to choose the best combination of such parameters and to optimize reflecting surface and radiation receiver. Photovoltaic module with cooling or without it, solar collector, photovoltaic thermal module, etc. may be applied as radiation receivers. Mathematical physics equations have been deduced that describe the specifics of incident radiation flux reflection from the concentrator's surface and falling onto that of radiation receiver. Concentration distribution has been estimated, for various concentrator design parameters and various positions of receiver axis in relation to the focus of reflecting surface, on the symmetry plane. The most effective concentrator designs characterized by 100% optical efficiency correspond to options where the focus of concentrator's reflecting surface is located inside radiation receiver. Analysis of design options using the developed theory is shown on examples for given values of average concentration ratio (2, 6, 8, 10, 15, 20, 50), as well as radius of radiation receiver, half concentrator aperture and distance between the focus line and the symmetry axis of radiation receiver in cross-section.